Psychological Foundations as the Basis for Differentiated Instruction and Formative Assessment Strategies in the Islamic Religious Education Curriculum - Whan Nurdiana; Tasman Hamami (Tarbiyah : Jurnal Ilmiah Kependidikan, 2026)
This study aims to explore the role of psychological principles in the development of the Islamic Religious Education (PAI) curriculum, especially in strengthening differentiation learning strategies and formative assessments that are adaptive to the needs of students. Using a library research approach with a qualitative descriptive method, this study examines various academic literature such as books, articles, and relevant scientific documents. The analysis is carried out through content analysis techniques to obtain a deep and systematic understanding. The focus of the discussion is directed at how psychological approaches such as humanistic, constructivist, behavioristic, metacognitive, and sociocultural can be used as the foundation of a student-oriented curriculum. The results of the study show that the integration of psychological principles in the PAI curriculum is able to create more inclusive, reflective, and contextual learning, as well as provide space for teachers to adjust teaching and evaluation strategies according to the characteristics of students in providing assessments in a formative manner. This research contributes to providing educational services fairly and evenly without discrimination with methods tailored to the needs of students and measurable assessments through psychological principles with humanistic, constructivistic, behavioristic, sociocultural, and metacognitive approaches.